OSoMe: The IUNI observatory on social media - Davis, Clayton A; Ciampaglia, Giovanni Luca; Aiello, Luca Maria; Chung, Keychul; Conover, Michael D; Ferrara, Emilio; Flammini, Alessandro; Fox, Geoffrey C; Gao, Xiaoming; Gonçalves, Bruno; Grabowicz, Przemyslaw A; Hong, Kibeom; et al. (PeerJ Preprints, 2016)
The study of social phenomena is becoming increasingly reliant on big data from online social networks. Broad access to social media data, however, requires software development skills that not all researchers possess. Here we present the IUNI Observatory on Social Media, an open analytics platform designed to facilitate computational social science. The system leverages a historical, ongoing collection of over 70 billion public messages from Twitter. We illustrate a number of interactive open-source tools to retrieve, visualize, and analyze derived data from this collection. The Observatory, now available at osome.iuni.iu.edu, is the result of a large, six-year collaborative effort coordinated by the Indiana University Network Science Institute.
Keywords: Social media; Observatory; Twitter; Web Science; Network Science; Meme diffusion; Computational Social Science; Big data; API; OSoMe